Perspectives on the Old Saxon Heliand : introductory and critical essays, with an edition of the Leipzig fragment - Pakis, Valentine A. (Medieval European studies ;, 2010)
Heliand, the Old Saxon poem based on the life of Christ in the Gospels, is now readily available to students of Anglo-Saxon culture, history, linguistics, literature, and religion. In Perspectives on the Old Saxon Heliand, Valentine Pakis brings together recent scholarship to address new turns in the field and engage with relevant academic arguments of the past three decades. Furthering the ongoing critical discussion of both text and culture, this volume reflects the current state of medieval studies while demonstrating its evolution since the 1970s. --Book Jacket.